Transcriptome Dynamics Underlying Chlamydospore Formation in Trichoderma virens GV29-8 - Peng, Xinhong; Wu, Beilei; Zhang, Shuaihu; Li, Mei; Jiang, Xiliang (Frontiers in Microbiology, 2021)
Chlamydospores are a type of survival propagule used by many fungi, such as Trichoderma, that have thick walls and are resilient against adverse environmental conditions, properties that can be translated into improving biocontrol formulations through increasing shelf life and enduring various storage conditions. However, large-scale production of chlamydospores has proven difficult. To understand the molecular mechanisms governing chlamydospore formation (CF) in Trichoderma fungi, we performed a comprehensive analysis of transcriptome dynamics during CF across 8 different developmental time points, which were divided into 4 stages according to PCA analysis: the mycelium growth stage (S1), early and middle stage of CF (S2), flourishing stage of CF (S3), and late stage of CF and mycelia initial autolysis (S4). A total of 6462 differentially expressed genes (DEGs) were obtained by pairwise comparisons with samples of 4 adjacent stages. We identified the pathways and substances that play important roles in each stage of CF by GO, KEGG, STC and WGCNA analysis. The results showed that mycelial assimilation and absorption in the early growth stage exhausted some nutrients in the medium, resulting in nitrogen deficiency. At the same time, secondary metabolites and active oxygen free radicals released during mycelial growth produced an adverse growth environment. The resulting nitrogen-deficient and toxin enriched medium may stimulate cell differentiation by initiating cell cycle regulation to induce morphological transformation of mycelia into chlamydospores. During the mycelium growth and early stages of CF, high expression of genes involved in pathways related to glycogen and lipid decomposition promoted the breakdown of culture nutrients, providing energy for fungal growth and sporulation. On the contrary, high expression of genes relating to glycogen and lipid synthetic metabolic pathways during the flourishing and late stages of CF was conducive to energy storage in chlamydospores to provide energy for spore germination under favorable conditions. High expression of genes in the mannan and chitin synthesis pathways promoted the accumulation of mannan and chitin, components necessary for cell wall construction during the flourishing and late stages of CF. Our results provide a new perspective for understanding the genetics of biochemical pathways involved in CF of Trichoderma spp.